2017
DOI: 10.15850/amj.v4n2.1068
|View full text |Cite
|
Sign up to set email alerts
|

Level of Activity Daily Living in Post Stroke Patients

Abstract: Background: Stroke is the leading cause of disability and dependency which directly decrease patient'slife quality . Disability caused by stroke can be prevented by holistic and comprehensive management plan of stroke. Until now, there was no study conducted to evaluate management for post stroke patients in Dr. Hasan Sadikin General Hospital (RSHS). Therefore, this studyaimed to describe level of activities of daily living (ADL) in post stroke patients in Neurology unit of RSHS as a basic evaluation for a bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“… 1 , 2 Impairment of ADL independence can result in patients having decreased quality of life and social participation. 3 ADL independence is affected by neurological impairments, including motor weakness, sensory loss, language dysfunction, and impaired consciousness. 3 , 4 Among the neurological impairments, motor weakness can be mainly caused by the corticospinal tract (CST) injury, the most important neural tract for motor function in the human brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 Impairment of ADL independence can result in patients having decreased quality of life and social participation. 3 ADL independence is affected by neurological impairments, including motor weakness, sensory loss, language dysfunction, and impaired consciousness. 3 , 4 Among the neurological impairments, motor weakness can be mainly caused by the corticospinal tract (CST) injury, the most important neural tract for motor function in the human brain.…”
mentioning
confidence: 99%
“… 3 ADL independence is affected by neurological impairments, including motor weakness, sensory loss, language dysfunction, and impaired consciousness. 3 , 4 Among the neurological impairments, motor weakness can be mainly caused by the corticospinal tract (CST) injury, the most important neural tract for motor function in the human brain. 5 Many studies have demonstrated differences in motor function according to the state of the ipsilesional CST in patients with stroke.…”
mentioning
confidence: 99%
“…The most common neurological dysfunctions caused by stroke include mobility, speech problems and the inability to perform activities of daily living (ADL) (Ramos-Lima et al 2018 ), such as home management, self-care, work and social roles (Ahn & Hwang 2018 ). As a result of decreased physical functioning, stroke survivors may find it difficult to actively participate or engage in social activities (Whitiana, Vitriana & Cahyani 2017 ). This may lead to social isolation and contribute to depression and feelings of helplessness (Brookfield & Mead 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Upon discharge, stroke survivors are often cared for by their families who ensure that the home environment is conducive enough to support the recovery process (Whitiana et al 2017 ). When first receiving the stroke diagnosis, the family is often confused and worried about the life of their family member.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also argue that the above conditions can trigger recurring CVAs due to falls or severe stiffness (Park et al, 2016). The most frequently disrupted physical activity in CVA patients is activities of daily living, such as the ability to eat, bathe, dress up, and move their upper and lower limbs (Whitiana et al, 2017).…”
Section: Introductionmentioning
confidence: 99%